Analisis Pembelajaran Fisika: Dari Sudut Pandang Guru Dan Siswa - Purnomo, Dian; Rian Vebrianto; Rohani; Adisti Yuliastrin (Lamda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
One of the main problems in the world of education is the weak learning process. Learning in the classroom tends to only teach memorization of information without connecting it to applications in everyday life. The purpose of this research is to find out problems related to material that are considered difficult and how to solve these learning in physics learning at MTS. The methodology of this study uses a mixed method ̧ where quantitative data is then strengthened with qualitative data. In this study, 2 science teachers, 30 students of grade VII MTS. This study uses interview, observation, and questionnaire instruments. Data is collected by directly going down to the field and analyzed using descriptive analysis for quantitative and qualitative analysis of interview results so that the data obtained becomes comprehensive. The results showed that students had difficulty distinguishing principal and derivative quantities (60%), understanding unit conversions (70%), writing unit symbols correctly (50%), and using measuring tools (57%). After applying Canva-based experimental video media, there was an increase in students' understanding of physics concepts, with an increase in understanding of principal and derivative quantities from 40% to 80%, unit conversion from 30% to 75%, and skills using measuring tools from 43% to 78%. The conclusion of this study is that the use of Canva-based interactive media can be an effective solution in improving students' understanding of the concept of quantities and units, especially for schools that have limited laboratory facilities.